2011
DOI: 10.1098/rstb.2010.0187
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention and stability

Abstract: In the present review, we address the relationship between attention and visual stability. Even though with each eye, head and body movement the retinal image changes dramatically, we perceive the world as stable and are able to perform visually guided actions. However, visual stability is not as complete as introspection would lead us to believe. We attend to only a few items at a time and stability is maintained only for those items. There appear to be two distinct mechanisms underlying visual stability. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 99 publications
(196 reference statements)
6
70
1
1
Order By: Relevance
“…We varied the time of target presentation with respect to the saccade in order to test whether predictive remapping might influence the processing of the target stimulus. We found that the discrimination of the target stimulus increased dramatically when it was presented shortly before a saccade [59]. In other words, the intention to make a saccadic eye movement 'unmasked' the target, even when both target and mask were shown in the same retinal position.…”
Section: Neural Mechanisms Of Visual Stability: Remapping and Spatiotopymentioning
confidence: 77%
See 1 more Smart Citation
“…We varied the time of target presentation with respect to the saccade in order to test whether predictive remapping might influence the processing of the target stimulus. We found that the discrimination of the target stimulus increased dramatically when it was presented shortly before a saccade [59]. In other words, the intention to make a saccadic eye movement 'unmasked' the target, even when both target and mask were shown in the same retinal position.…”
Section: Neural Mechanisms Of Visual Stability: Remapping and Spatiotopymentioning
confidence: 77%
“…In addition, a number of interesting effects have been reported which are neither spatiotopic nor retinotopic in nature [8,58,59]. For example, we recently tested shape discrimination for a brief target that was followed by a mask.…”
Section: Neural Mechanisms Of Visual Stability: Remapping and Spatiotopymentioning
confidence: 99%
“…There is much evidence that only attended objects are remapped (e.g. [43]), and several other chapters in this issue highlight the importance of attention in visual stability and remapping, particularly Wurtz et al [44] and Mathô t & Theeuwes [45].…”
Section: Spatiotopicitymentioning
confidence: 97%
“…For example, Mathô t & Theeuwes [45] believe that the 'anticipatory RF shift allows neurons to take a 'sneak peak' at the location which will be brought into the RF'. Similarly, Wurtz et al [44] suggest that 'comparing the activity in the RF after the saccade to the activity in the future RF before the saccade is a potential mechanism that might underlie the perception of visual stability'.…”
Section: Neurons With 'Shifting Receptive Fields'mentioning
confidence: 99%
“…We investigated whether feature-based attention plays a role in landmark search. In this framework, attention selects the saccade target that serves as a landmark pattern (Mathôt & Theeuwes, 2011) and is involved in the search for that target once the eyes land.…”
mentioning
confidence: 99%